2021
DOI: 10.3390/w13223163
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Response of the Kunhar River Basin in Pakistan to Climate Change and Anthropogenic Impacts on Runoff Characteristics

Abstract: Pakistan is amongst the most water-stressed countries in the world, with changes in the frequency of extreme events, notably droughts, under climate change expected to further increase water scarcity. This study examines the impacts of climate change and anthropogenic activities on the runoff of the Kunhar River Basin (KRB) in Pakistan. The Mann Kendall (MK) test detected statistically significant increasing trends in both precipitation and evapotranspiration during the period 1971–2010 over the basin, but wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The decreasing trend in total annual, seasonal (winter and monsoon) precipitation, intensity-based indices, and frequency-based indices indicate that the overall frequency and severity of extreme precipitation events are reducing over time and space [2, 17, PLOS ONE 25,30,39]. This pattern can be related to the ongoing consequences of climate change, including increased temperatures, changing air circulation patterns, and decreased soil moisture levels [31,40,41]. These factors are leading to changes in precipitation patterns and intensities, with wet regions becoming drier and dry regions becoming even more arid [42].…”
Section: Discussionmentioning
confidence: 99%
“…The decreasing trend in total annual, seasonal (winter and monsoon) precipitation, intensity-based indices, and frequency-based indices indicate that the overall frequency and severity of extreme precipitation events are reducing over time and space [2, 17, PLOS ONE 25,30,39]. This pattern can be related to the ongoing consequences of climate change, including increased temperatures, changing air circulation patterns, and decreased soil moisture levels [31,40,41]. These factors are leading to changes in precipitation patterns and intensities, with wet regions becoming drier and dry regions becoming even more arid [42].…”
Section: Discussionmentioning
confidence: 99%
“…In Equation ( 2), variables P and Q are quite general and can be used as instantaneous, monthly, or annual values [77][78][79]. In this study, the mean annual values of streamflow Q and precipitation P for the estimation of ε p were utilized.…”
Section: Np (Np) Bivariate Modelmentioning
confidence: 99%
“…Similarly, it was also found that the regression analysis that includes temperature improves the coefficient of determination (R 2 ) [40]. Since all the subsequent research based on multivariate models suggests that multivariate models are more reliable than bivariate elasticity models [39,42,48,[73][74][75][76][77][78][79][80][81][82], it is believed that the multivariate elasticity results of our study are more authentic than the bivariate elasticity results, although there is very small difference between the results as discussed in Section 3.1 above.…”
Section: Bivariate Versus Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, at higher elevations or latitudes, climate change is expected to weaken the modulating effect of snow and glacier fields, with possibly strong impacts on hydropower generation, floods and droughts, irrigation water supplies, and associated food production [9]. Moreover, the variability of a hydrological regime is strongly affected by anthropogenic actions such as irrigation, urbanization, and recreational activities [10]. In particular, land cover change is a dominant factor affecting ecosystems [11,12] and the hydrological regime [13].…”
Section: Introductionmentioning
confidence: 99%